2017
DOI: 10.5326/jaaha-ms-6506
|View full text |Cite
|
Sign up to set email alerts
|

Dilated Cardiomyopathy in Standard Schnauzers: Retrospective Study of 15 Cases

Abstract: Dilated cardiomyopathy (DCM) is the most common myocardial disorder of dogs, typically affecting large and giant breeds. The purpose of this study was to describe the clinical features of DCM in standard schnauzers. Medical records for 15 standard schnauzers diagnosed with DCM were reviewed. The median age at diagnosis of DCM was 1.6 yr, with all dogs developing left-sided congestive heart failure (CHF). The median age of onset of CHF was 1.6 yr, and was significantly shorter in males (1.5 yr) than for females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Canine dilated cardiomyopathy (DCM) represents the second most common acquired heart disease in dogs and has multiple identified etiologies [1][2][3]. While DCM of genetic origins have been described for some breeds based upon discovered mutations or observed heritability and pattern of inheritance, determining etiology of DCM when observed outside of these breeds is challenging [4][5][6][7][8][9][10][11][12][13][14][15][16]. Nutritionally mediated DCM has been described across a variety of species including dogs and is most historically linked to taurine deficiency [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Canine dilated cardiomyopathy (DCM) represents the second most common acquired heart disease in dogs and has multiple identified etiologies [1][2][3]. While DCM of genetic origins have been described for some breeds based upon discovered mutations or observed heritability and pattern of inheritance, determining etiology of DCM when observed outside of these breeds is challenging [4][5][6][7][8][9][10][11][12][13][14][15][16]. Nutritionally mediated DCM has been described across a variety of species including dogs and is most historically linked to taurine deficiency [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Secondary DCM might be associated with toxic change, infectious agents, endocrinopathies, and nutritional disorder (3,5,9,17,18,22,24). Previous reports have shown that lower levels of taurine and carnitine (5,(9)(10)(11)17,18,20,26) could affect breeds such as Standard schnauzer (13) and Portuguese water dogs, especially Cocker Spaniels (3,9,(10)(11)(12)14,17,18,20,22,24,26). In addition, DCM may occur if a normal dog is supplied with less taurine and carnitine.…”
Section: Discussionmentioning
confidence: 99%
“…developing DCM over the past 15 years. In addition to external factors such as changes in breed popularity, infectious disease, and diet, it must be considered that an increase in atypical breeds may simply be a reflection of previously unrecognized heritable cardiomyopathies occurring in the breeds as seen with toy Manchester terriers, standard schnauzers, Welsh springer spaniels, Rhodesian ridgebacks, Dalmatians, and English bulldogs [31][32][33][34][35][36][37] Here, we describe a more than five-fold increase in grain-free pet food sales over the past decade, with no correlating increase in overall DCM incidence. The number of dogs currently eating grain-free diets is unknown, but we estimate it to be between 10-40% of the US dog population (Fig 5C).…”
Section: One Veterinary Hospital Provided Age Distribution Date Over mentioning
confidence: 99%